Hubungan Diabetes Mellitus dengan Penyakit Jaringan Periodontal pada Masyarakat Lahan Basah di Kabupaten Banjar, Provinsi Kalimantan Selatan - Emilda Sari; Ida Rahmawati; Irmanita Wiradona; Neny Setiawaty Ningsih; Descyana Hakim (Jurnal Ners, 2025)
the common complications associated with DM is periodontal disease, which involves inflammation and destruction of the tissues supporting the teeth. This study aims to examine the association between DM and periodontal disease status in the wetland community of Banjar District, South Kalimantan. A cross-sectional observational analytic design was employed, involving 115 respondents. Fasting blood glucose levels were measured to determine DM status, and periodontal condition was assessed using the Periodontal Disease Index (PDI). The results revealed that 76.8% of respondents with DM exhibited poor periodontal health, compared to only 37% of non-DM individuals. Statistical analysis using the Chi-Square test confirmed a significant relationship between DM and periodontal status (p = 0.000). These findings indicate a strong correlation between diabetes and increased risk of periodontal disease. Therefore, targeted oral health education and preventive dental care are essential components of diabetes management, especially in wetland communities where access to dental services may be limited. This study underscores the need for integrated public health strategies that address both systemic and oral health issues among vulnerable populations.